The dynamic of the changes of the motoric features and physical fitness in the group of the children training the acrobatic - Szyszka, Dorota; Majewska, Małgorzata; Pietrzykowska, Barbara; Stanoch, Małgorzata (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
The goal of that publication is to assess the tempo and dynamics of the basic somatic changes and physical fitness among young students – acrobats within 3 - year observation. The source of the study are the results of the longitudinal research conducted in the primary sports school no 69 in Poznań. The children are trained there within 3 year program continuously. The research covers the students from the sports classes and the students from the ordinary classes, attending the same primary school. The detailed analysis of the results shows, that the improved level of the sports activity, involving the systematic and dedicated physical training of the initial and basic acrobatics exercises does not considerably influence the differences of the tempo and the dynamic of the improvement of the certain physical features and physical fitness between the sports class students and control group.